Consumer Perceptions to the Agro-tourism of Red Dragon Fruit Palopat Maria - Evahelda Evahelda; Rati Purwasih; Parlindungan Siregar (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
The consumer perceptions are interesting to be inspected because the perceptions of each consumer will vary even though they are in the same place and situation. This research aimed to determine consumer perceptions to the agro-tourism of red dragon fruit Palopat Maria in terms of service, facilities and attractiveness. The research method used was the case study method. The sampling method that used was accidental sampling with 30 respondents who came to Red Dragon Fruit Palopat Maria Agro-tourism. Furthermore, the data obtained were analyzed using descriptive statistics. The results showed that consumers gave a perception score of 4.13 for services, 3.19 for facilities, and 4.33 for attractiveness, it means that consumers gave good perceptions for services and facilities, also very good perceptions for the attractiveness of Red Dragon Fruit Palopat Maria Agro-tourism. The agro-tourism parties need to improve services such as employee uniforms and improve facilities such as providing directions to the agro-tourism location.